VPAC receptor positivity in comparison with mp‐MRI in the diagnosis of prostate cancer: A preliminary study - Nishant Setya; Shridhar C. Ghagane; Rajendra B. Nerli; Ashwin Bokare; Madhukar L. Thakur; Leonard Gomella (BJUI Compass)
Abstract Objective The study aimed to prospectively evaluate the feasibility of diagnosing PCa using voided urine samples and by targeting the genomic VPAC (vasoactive intestinal peptide and pituitary adenylate cyclase‐activating peptide) receptors in comparison with multiparametric magnetic resonance imaging (mp‐MRI) in male patients (≥40 years of age) with lower urinary tract symptoms and having a serum PSA of >4 but <15 ng/ml. Patients and Methods Male patients attending urological services ≥40 years old, with lower urinary tract symptoms and serum PSA levels of >4 but <15 ng/ml formed the study group. Voided urine samples were collected to target VPAC receptors on malignant cells. All patients underwent mp‐MRI. A 12‐core transrectal ultrasound‐guided prostate biopsy was performed in all, and the results were compared for the diagnosis of PCa. Results A total of 61 patients with a median age of 65.33 ± 8.11 years and with a median serum PSA of 9.56 ± 2.78 ng/ml were further evaluated with both urinary biomarker assessment and mp‐MRI. Histopathological (HPR) confirmation of PCa was noted in 25 (40.98%) patients and benign prostatic hyperplasia in the remaining 36 (59.01%) patients. Of the 25 patients with histologically proven PCa, the urinary biomarker (VPAC positivity) was positive for malignancy in 24 (96%), one case showed false negative results (4%) and there were no false positive cases (0%). HPR confirming PCa was seen in 3/16 patients with a PIRADS 2 score, 7/21 patients with a PIRADS 3 score, 7/14 patients with a PIRADS 4 score and 8/8 patients with a PIRADS score of 5. Conclusions VPAC receptor positivity of prostate cancer cells is an easy test to perform using a voided urine sample. VPAC receptor positivity can be used as an indication for prostate biopsy in patients having a negative previous biopsy but highly suspicious of cancer, in patients with an elevated serum PSA but with a normal digital rectal examination and in patients with benign features and borderline elevation of serum PSA.